Work ability of employees with disabilities in Malaysia - Lavasani, Seyed Sobhan; Abdul Wahat, Nor Wahiza; Ortega, Adriana (Asia Pacific Disability Rehabilitation Journal, 2015)
Purpose: Based on a sample of employees with disability, this study aimed to: (1) evaluate the construct validity of work ability index (WAI), core self-evaluation scale (CSES) and job in general index (JIG), in order to make a valid and reliable assessment of their work ability, job satisfaction and core self-evaluation; (2) assess their levels of work ability, job satisfaction, and core self-evaluation; (3) investigate the associations of work ability with job satisfaction and core self-evaluation among them; and (4) determine which demographic characteristics significantly affect the work ability of employees with disability.